RANCANG BANGUN MEDIA INFORMASI KEGIATAN PROFESI BIDAN DAERAH SUMBAWA BERBASIS ANDROID - Yuliastuti, Luh Putu Sri; Widiarta, I Made (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
The advancement of information and communication technology impacts various fields, including healthcare services. The Indonesian Midwives Association (IBI), as a professional organization for midwives in Indonesia, plays a role in enhancing the professionalism of its members to ensure quality healthcare services. This study aims to develop an Android-based application to disseminate information about IBI activities in the Sumbawa region, facilitating public access to midwifery services. The application development process includes system analysis, design, implementation, and testing using the blackbox testing method. The application features five main functions: activity news, event agendas, information about midwives, organizational profiles, and links to IBI-related websites. Test results indicate that each feature operates as intended. This application is expected to serve as an effective information medium, improving public access to healthcare services, particularly in the midwifery field, and supporting IBI activities in providing more transparent and integrated services.